(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the relevance of the study is due to the problem of degradation of the health of the population, especially students. It is generally recognized that one of the most important risk factors for the formation of diseases of the cardiovascular and other functional systems of the body of adolescents, while the level and mode of physical activity appropriate for age and health status is a powerful factor in disease prevention and health promotion